Effects of particulate matter on allergic respiratory diseases. Issue 2 (June 2018) - Wu, Jin-Zhun; Ge, Dan-Dan; Zhou, Lin-Fu; Hou, Ling-Yun; Zhou, Ying; Li, Qi-Yuan
Abstract: The health impact of airborne particulate matter (PM) has long been a concern to clinicians, biologists, and the general public. With many epidemiological studies confirming the association of PM with allergic respiratory diseases, an increasing number of follow-up empirical studies are being conducted to investigate the mechanisms underlying the toxic effects of PM on asthma and allergic rhinitis. In this review, we have briefly introduced the characteristics of PM and discussed its effects on public health. Subsequently, we have focused on recent studies to elucidate the association between PM and the allergic symptoms of human respiratory diseases. Specifically, we have discussed the mechanism of action of PM in allergic respiratory diseases according to different subtypes: coarse PM (PM2.5-10 ), fine PM (PM2.5 ), and ultrafine PM.